Power line communication systems for smart grids - Casella, Ivan R. S.; Anpalagan, Alagan (IET energy engineering series, 2018)
This book aims to present a comprehensive introduction to the basic principles involved in the use of power line communications (PLCs) in the ICT infrastructure of smart grids (SGs) and show how they can benefit from these technologies to improve energy monitoring, control, security and management, especially when renewable energies sources are employed. The development of the ICT infrastructure of the SGs using PLC technologies is extremely complex since it involves the joint knowledge of the areas of communication and energy, which are areas that are not normally treated together. Thus, this book has been organized to cover from basic concepts of modern digital communications, important coding techniques, specific features of PLC channels and the fundamentals of SGs, to the differences between narrowband PLC (NB-PLC) and broadband PLC (BB-PLC) technologies for SG applications, major PLC standards and some state-of-the-art works. It was conceived with a more didactic approach to some fundamental topics in order to be useful not only to researchers but also to students, academics and engineers.